Walker Evans starting from scratch - Alpers, Svetlana 1936- (Princeton University Press, 2020)
"A magisterial study of celebrated photographer Walker Evans"--
Keywords: Evans, Walker -- 1903-1975; Dokumentarfotografie; Evans, Walker / 1903-1975 / Criticism and interpretation; Photography, Artistic; Documentary photography / United States; Evans, Walker / 1903-1975; Documentary photography; United States; Criticism, interpretation, etc